Impact of meconium-stained amniotic fluid on mode of delivery and maternal and neonatal outcome in a tertiary care hospital: a cross-sectional study - Jananni A., Vedha; Chhatwal, Jasbir G.; Kandasamy, Vijayalakshmi; Shinde, Ranoji V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Meconium-stained amniotic fluid during labour has been long considered the predictor of adverse foetal outcomes such as meconium aspiration syndrome and perinatal asphyxia, which leads to perinatal and neonatal morbidity and mortality. Hence this study was done to compare the mode of delivery and neonatal complications among deliveries complicated by meconium-stained liquor with that of clear liquor. Methods: The present study was a hospital based cross sectional study carried out in the department of obstetrics and gynaecology, Chettinad Hospital and Research Institute, Chennai, India. The study was carried out for a period between February 2022 and January 2023 among the pregnant women, who were admitted for delivery. Results: A total of 110 deliveries with meconium-stained liquor was included and out of whom, 57% (63) were with thin meconium and 43% (47) had thick meconium. It was observed that 25.5% of the babies born out of thick MSL needed ICU admission for resuscitation efforts whereas 7.9% babies born out of thin MSL needed NICU admission. Conclusions: The study observed that deliveries associated with thick meconium-stained liquor were at an increased risk of respiratory distress of the child, NICU admission in the child and were prone for more emergency LSCS when compared to thin MSL deliveries.